Redesigning the Production Warehouse and Packaging House at the Agricultural Office of the Main Hall of Food Crops and Horticultural in Banten Province - Darwis, Zulmahdi; Fathonah, Woelandari; Kuncoro, Hendrian Budi Bagus; Zulfathir, Reza (Jurnal Fondasi, 2023)
The Banten Provincial Agriculture Office aims to repurpose an existing storage warehouse into a packaging warehouse and production facility for food products. This study focuses on assessing the structural performance of the building and determining its suitability for the new functions. Utilizing the Load and Resistance Factor Design (LRFD) method, the strength of the current structure is evaluated under the anticipated loads. The analysis reveals that while most elements of the building meet the required standards, the existing columns are unable to support the intended load. Based on calculations, the nominal compressive strength value of the existing IWF column is determined to be 202.462 kN, falling short of the required strength of 255.075 kN. To address this, a recommendation is made to reinforce the columns by wrapping their steel profiles with reinforced concrete, transforming them into composite columns with a nominal compressive strength capacity of 1678.24 kN. This reinforcement approach ensures that the building can effectively accommodate the packaging and production operations for food products. The findings of this study provide essential guidance for the Banten Provincial Agriculture Office in making informed decisions on the necessary structural improvements. By implementing the proposed reinforcement measures, the building's structural integrity is enhanced, prolonging its service life and ensuring its suitability for the intended functions.